Kajian Literatur: Peran Program Tahfidzul Qur’an dalam Membentuk Kedisiplinan Belajar Santri di Pondok Pesantren - Khoirin, Taufiq; Subando, Joko (TSAQOFAH, 2025)
The tahfidzul Qur’an program is an integral component of the pesantren education system, aimed not only at producing Qur’an memorizers but also at cultivating students’ character and discipline in the learning process. This article explores the relationship between the implementation of the tahfidz program and the development of students’ learning discipline through a literature review approach. The method employed is a library study of relevant literature on pesantren education, character formation, and learning theories. The findings indicate that the tahfidz program significantly contributes to discipline development through routine practice, role modeling by ustadz, and a structured and consistent coaching system. The application of behaviorist approaches and the integration of character education within tahfidz activities encourage students to develop consistency, focus, and a sense of responsibility in their studies. The study concludes that strengthening the tahfidzul Qur’an program within the pesantren curriculum is an effective strategy for shaping religious, strong-charactered, and disciplined students in their pursuit of knowledge.